Benefit–risk management in the age of personalized healthcare. (July 2012) - Forstner, Michael
The ongoing developments in personalized healthcare are opening new possibilities for the optimization of the benefit–risk profiles of drugs based on the stratification of patients. Beyond this straightforward application of pharmacogenomics to the optimization of benefit–risk profiles, other approaches, such as metabolomics and systems pharmacology, may contribute to an improved use of medicines in a personalized healthcare setting. These will, however, require fundamental adaptations or new developments in various areas and by all stakeholders, including the pharmaceutical and diagnostics industries, regulators, physicians and patients. Ultimately, personalized healthcare should enable patients to take personal decisions on treatment options based on their preferred benefit–risk profiles of therapeutics.